Apk Absensi Dengan Kolaborasi Fingerprint Dan SMS Gateway Menggunakan Framework Codeignitier Pada SMKN 1 Lobalain, Rote Ndao - Leuhoe, Yermias Jaher Ite; Sesun, Robert Nomensen (Jurnal Informatika UPGRIS, 2022)
Vocational High School (SMK) Negeri 1 Lobalain is one of the formal education channels that provides vocational education at the secondary education level located in Rote Ndao Regency, East Nusa Tenggara Province. In improving education, cooperation from parents is needed because educating students to be disciplined is not only the responsibility of the school, but parents must also be actively involved in monitoring student attendance. One of the things that must be improved in improving the quality of education is attendance. The problem at SMK Negeri 1 Lobalain is the student attendance system which is done manually so that it has an impact on attendance manipulation. As technology develops rapidly, fingerprint technology provides attendance and avoids the manipulation of attendance data. Based on the problems that have been defined, the author aims to make an attendance Apk with fingerprints and an SMS gateway using the Codeigniter Framework, it is hoped that by making this Apk it can help schools and parents in improving the quality of education at SMKN 1 Lobalain.